(untitled) (World Bulletin of Management and Law, 2022)
This article legally analyses sexual harassment as one of the most harmful forms of violence against women in the context of work. The concept of sexual harassment in the workplace was discussed from different points of view. In addition, the article analyses how the workplace harassment in the organizations in Uzbekistan and other neighboring countries find its basis in the legislation. It also studies the consequences of harassment for the victims, in the organizational context where it takes place. Finally, it problematizes harassment in the general continuum of violence experienced by women.